2012
DOI: 10.1021/jp211689z
|View full text |Cite
|
Sign up to set email alerts
|

CO2 in 1-Butyl-3-methylimidazolium Acetate. 2. NMR Investigation of Chemical Reactions

Abstract: The solvation of CO(2) in 1-butyl-3-methylimidazolium acetate (Bmim Ac) has been investigated by (1)H, (13)C, and (15)N NMR spectroscopy at low CO(2) molar fraction (mf) (x(CO(2)) ca. 0.27) corresponding to the reactive regime described in part 1 of this study. It is shown that a carboxylation reaction occurs between CO(2) and Bmim Ac, leading to the formation of a non-negligible amount (~16%) of 1-butyl-3-methylimidazolium-2-carboxylate. It is also found that acetic acid molecules are produced during this rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
91
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(104 citation statements)
references
References 51 publications
12
91
0
1
Order By: Relevance
“…has been reported previously by Besnard et al (2012) and Kortunov et al (2015), who showed that the signal at 141.5 ppm corresponds to the carboxylated C3 position in EMIM ? .…”
Section: Chemical Structures Of Dissolved and Regenerated Cellulosesupporting
confidence: 68%
See 1 more Smart Citation
“…has been reported previously by Besnard et al (2012) and Kortunov et al (2015), who showed that the signal at 141.5 ppm corresponds to the carboxylated C3 position in EMIM ? .…”
Section: Chemical Structures Of Dissolved and Regenerated Cellulosesupporting
confidence: 68%
“…These findings indicate that a possible reaction takes place between the cellulose-sorbed CO 2 and the EMIM?, yielding a carboxylated EMIM ? with characteristic NMR signals (Besnard et al 2012;Kortunov et al 2015) coincident with the signals observed at 154.3 and 141.5 ppm. It is, however, important to bear in mind that the carbonate band seen in the ATR-IR spectroscopy in which no EMIMAc was present shows that the signal at 154.3 ppm does not originate from the EMIMAc but is introduced during the dissolution of cellulose in NaOH(aq).…”
Section: Chemical Structures Of Dissolved and Regenerated Cellulosesupporting
confidence: 64%
“…Limitless combinations of cation and anion that form the ionic liquids lead to different physical properties and phase behavior, thus allowing ionic liquids to be labeled as "designer" solvents. Although most works on this subject deal with imidazolium-based ionic liquids these have several limitations in what concerns their thermal and chemical stability, price, toxicity and biodegradability [2][3][4][5][6][7]. To overcome these issues, ions derived from natural resources have emerged as completely bio-derived ionic liquids, such as cholinium-based ionic liquids.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22][23] A reactive mechanism has been proposed in which the proton bounded to carbon atom 2 of the imidazolium cation is released leading to the generation of a carbene intermediate, whereas the proton interacts with the acetate anion to form acetic acid (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Other works, although considering the formation of carbene and acetic acid, differ slightly from this initial interpretation, arguing that the reactions are triggered by the introduction of carbon dioxide itself in the IL and that the carbene and carboxylate formation results from a concerted cooperative process between the cation, the anion, and the CO 2 molecule. [20][21][22] More recently, it was theoretically inferred that it is the introduction of neutral molecules like CO 2 in the IL charged network which cancels partially the charge-stabilizing effect existing in the neat IL and that this so-called inverse ionic liquid effect facilitates the carbene formation and, thus, the chemical absorption. 24,25 Very recently, new insights in the understanding of solute-solvent interactions within IL were provided from a theoretical study on the solvation of a carbene 1-ethyl-3-methylimidazole-2-ylidene in 1-ethyl-3-methylimidazolium acetate.…”
Section: Introductionmentioning
confidence: 99%